Optimization of Resistance Band Exercise to Reduce Blood Pressure in Hypertension: Systematic Review - Yuliyanti Permane Suci; Endang Triyanto (GLOBAL HEALTH SCIENCE GROUP, 2024)
Hypertension is a chronic disease that is often found throughout the world and is a major risk factor for cardiovascular disease. Non-pharmacological approaches such as physical exercise, including resistance band exercises, can be effective in lowering blood pressure. However, the effectiveness of resistance band training in managing hypertension still requires further research. This article aims to assess the effectiveness of resistance band training in reducing blood pressure in individuals with hypertension. We conducted a systematic review of articles published in the period 2010-2023 using four main databases, namely PubMed, Scopus, Google Scholar, and the Cochrane Library, for articles discussing the use of resistance band exercises in hypertensive individuals with the search keywords being hypertension and resistance band exercise and combining Boolean operators (or, and, not) to achieve a more complete search. Three independent reviewers analyzed the articles based on predefined inclusion and exclusion criteria. Through the initial search, 2,785 articles were found. Based on the PRISMA flowchart and after manual review, only 10 studies met the inclusion criteria and were identified for further analysis. The results of the review show that resistance band exercises performed regularly, especially for 8 weeks or more, can reduce systolic and diastolic blood pressure in individuals with hypertension. This exercise was proven to be effective in reducing blood pressure, and this effect was more significant in the group that followed a regular exercise program. Significant changes in blood pressure were noted during an exercise program performed 2-3 times a week at moderate intensity. Resistance band training can be an effective non-pharmacological alternative in managing hypertension and has the potential to be part of the long-term management of hypertension. However, further research is needed to determine the optimal duration, intensity and frequency of exercise for maximum results.